Detection of a Serratia sarumanii outbreak in neonatal intensive care units using SaTScan and whole genome sequencing, Philippines, 2022 - Godin, Giselle V; Sia, Sonia B; Ablola, Ferissa B; Gayeta, June M; Lagrada, Marietta L; Macaranas, Polle Krystle V; Olorosa, Agnettah M; Palarca, Janziel Fiel; Jamoralin Jr, Manuel C; Borlasa, June Janice; Gacho, Ma Fe Laren B; Andico, Rica Marie B; et al. (Western Pacific Surveillance and Response, 2026)
Objective: This study aimed to demonstrate the benefits of using SaTScan (Boston, MA, USA), a cluster-detection software programme, and whole genome sequencing to investigate a suspected outbreak of Serratia marcescens infections in a tertiary government hospital in the southern Philippines. The hospital is part of the national Antimicrobial Resistance Surveillance Program’s network of sentinel sites. Methods: The investigation followed national outbreak investigation protocols. In May 2022, when evaluation of daily hospital laboratory census data revealed an increase in the number of Serratia species in the hospital, an alert was triggered. A concurrent, routine SaTScan analysis of the hospital’s surveillance data by the Antimicrobial Resistance Surveillance Reference Laboratory confirmed a cluster of cases. The Reference Laboratory requested isolates from clinical specimens from the hospital for confirmation of bacterial identification, antimicrobial susceptibility testing and whole genome sequencing. Results: Six isolates were submitted for genomic analysis, two of which were from the identified cluster. Although originally identified as S. marcescens, five of the isolates were subsequently confirmed as S. sarumanii. Phylogenetic analysis showed that the two isolates from the cluster were closely related and belonged to the same clade, which may suggest a common source. Three antimicrobial resistance genes were identified, but their phenotypic expression was limited, with one isolate exhibiting resistance mechanisms. Discussion: This study highlighted the utility of SaTScan for the early detection of potential disease outbreaks. The use of whole genome sequencing enhanced the investigation by enabling the analysis of potential transmission pathways at the genetic level, identification of the outbreak source and the detection of novel species.